Insectivorous bat activity dataset across different land-use types in the Islands of São Tomé and Príncipe, Central West Africa - Ana Filipa Palmeirim; Ana Catarina Araújo-Fernandes; Ana Sofia Castro-Fernandes; Patricia Guedes; José Cassari; Vanessa A. Mata; Natalie Yoh; Ricardo Rocha; Javier Martínez-Arribas; Fernanda Alves-Martins (Biodiversity Data Journal, 2024)
São Tomé and Príncipe oceanic islands, in Central West Africa, are characterised by exceptional levels of endemism. Since human colonisation in the mid-15th century, São Tomé and Príncipe have lost 74% and 67% of their native habitat, respectively. Today, these islands are mainly covered by remaining old-growth forests, secondary regrowth forests, shaded plantations (mostly of cocoa), oil palm plantations (in the case of São Tomé), small-scale agricultural areas and urban areas. Yet, little is known about how species on these islands are coping with land-use changes. Island ecosystems are particularly important for bats, with about 25% of the world’s bat species being entirely restricted to island systems. São Tomé and Príncipe Islands comprise six and four native insectivorous bats, respectively. Two species, Chaerephon tomensis and Macronycteris thomensis, are island-endemics in São Tomé; Pseudoromicia principis is an island-endemic in Príncipe; and Miniopterus newtoni is endemic from both São Tomé and Príncipe. Here, we present a dataset comprising a comprehensive compilation of occurrence records derived from acoustic sampling of insectivorous bats across the predominant land-use types of both the São Tomé and Príncipe Islands. In each sampling site, standardised surveys consisted of deploying one Audio Moth device that recorded for 1 minute every 5 minutes over a 48-hour period. We identified a total of 19,437 bat-passes across the 115 sites surveyed in São Tomé Island and 17,837 bat-passes across the 50 sites surveyed in Príncipe Island.Based on a sampling effort of 1,584 hours of recordings manually processed to identify all the contained bat passes, this dataset, publicly available on GBIF, provides comprehensive information on the activity of insectivorous bats across two endemic-rich oceanic islands in the Gulf of Guinea. For each bat pass identified, we report the identified species, geographic coordinates, land-use type, altitude, date and time. This is the first public dataset providing detailed information on species-level habitat use for insectivorous bats on oceanic islands in Africa.